2018
DOI: 10.5664/jcsm.7326
|View full text |Cite
|
Sign up to set email alerts
|

CPAP Therapy Delays Cardiovagal Reactivation and Decreases Arterial Renin-Angiotensin System Activity in Humans With Obstructive Sleep Apnea

Abstract: CPAP therapy was associated with delayed cardiovagal reactivation after a stressor and down-regulation of the arterial RAS. These findings may have important implications in mitigating cardiovascular risk in both men and women with OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Blood pressure as study outcome measure was reported in ten RCTs totaling 407 participants [18][19][20][21][22][24][25][26][27][28]30 and ten PCS containing 297 participants 34,36,[39][40][41][45][46][47][48] (Table 2). CPAP treatment led to a blood pressure reduction.…”
Section: Resultsmentioning
confidence: 99%
“…Blood pressure as study outcome measure was reported in ten RCTs totaling 407 participants [18][19][20][21][22][24][25][26][27][28]30 and ten PCS containing 297 participants 34,36,[39][40][41][45][46][47][48] (Table 2). CPAP treatment led to a blood pressure reduction.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies indicated that continuous positive airway pressure (CPAP) treatment improves autonomic function assessed by HRV after eliminating physiological influences (e.g. arousal, hypoxia and respiratory events) in OSA population [51,52]. Thus, further investigations on the interplay between neuro-metaboliccardiac networking and OSA-related physiological alternations are needed.…”
Section: Impact Of Impaired Hrvmentioning
confidence: 99%
“…Similarly, impaired vascular reactivity to different constrictor stimuli, such as Ang II and ET-1, has been reported in the aorta, as well as small mesenteric, cerebral and pulmonary arteries of CIH animal models ( 3 , 5 , 7 , 9 , 39 ). In individuals with OSA, arterial stiffness, as evaluated by the vasoconstrictor effects of intravenous Ang II challenge, was increased, which could be corrected by continuous positive airway pressure treatment ( 6 ). It was also found that the phosphorylation of p38 MAPK and ERK1/2 was increased by CIH, and the blockade of these kinases reduced Ang II-mediated contractions in both CIH aortic and mesenteric rings.…”
Section: Discussionmentioning
confidence: 99%
“…Obstructive sleep apnea (OSA) is a common disorder characterized by episodic arterial oxygen desaturation due to recurrent closure of the upper airway during sleep, namely intermittent hypoxia (IH), which can trigger excessive oxidative stress, systemic inflammation, sympathetic activation and increased renin generation, leading to abnormal vascular reactivity ( 1 , 2 ). IH-related vascular dysfunction involves impaired acetylcholine (ACh)-induced endothelium-dependent relaxation ( 3 , 4 ) and increased contractile responses to vasoconstrictors, such as angiotensin II (Ang II) ( 5 , 6 ) and endothelin-1 (ET-1) ( 7 9 ), which underlie the initiation and progression of hypertension. In our previous study, rats exposed to chronic IH (CIH) were found to exhibit enhanced Ang II-induced vasoconstriction, which was possibly attributed to the overactivation of ERK1/2 signaling through the upregulation of myosin phosphatase targeting subunit (MYPT1) and myosin light chain (MLC) phosphorylation ( 5 ).…”
Section: Introductionmentioning
confidence: 99%